Association of atopic diseases with atrial fibrillation risk: A systematic review and meta-analysis - Zeng, Rong; Wang, Jing; Liang, Ziting; Zhang, Jintao; Wang, Zihan; Xu, Changjuan; Dong, Liang (Frontiers in Cardiovascular Medicine, 2022)
Background: Atopic diseases and atrial fibrillation (AF) seem to share an underlying inflammatory pathology. To date, some population-based studies have explored the relationship between the two. We aimed to conduct a meta-analysis to examine the role of atopic condition in AF risk. Methods: All relevant observational studies in PubMed and EMBASE databases up to November 2021 were searched. In RevMan 5.3, we used random-effects or fixed-effects models to pool the effect sizes of hazard ratio (HR), odds ratio (OR) and their corresponding 95% confidence intervals (95% CI). In addition, I2 and Cochran Q test were used to evaluate the heterogeneity. Results: A total of 2488 records were retrieved. After screening according to the predetermined criteria, 6 cohort studies and 2 case-control studies were included in this meta-analysis. Herein, the meta-analysis of 6 cohort studies suggested that atopic diseases potentially increased the AF risk with the pooled HR of 1.26 (95%CI,1.14-1.39), while the pooled effect size (OR, 1.04; 95%CI,0.74-1.46) of 2 case-control studies was not statistically significant. Based on the types of atopic diseases, further subgroup analyses of 6 cohort studies revealed that asthma, allergic rhinitis, and atopic dermatitis all potentially increased the risk of subsequent AF with the pooled HR of 1.41 (n=4; 95%CI, 1.25-1.58), 1.12 (n=1; 95%CI,1.10-1.14) and 1.06 (n=3; 95%CI, 1.01-1.12), respectively. Conclusion: This meta-analysis demonstrated that patients with atopic diseases have a higher risk of developing AF, particularly those with asthma.